2013
DOI: 10.1039/c3lc50129a
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, label-free isothermal solid-phase amplification/detection (ISAD) device for rapid detection of genetic alteration in cancers

Abstract: Here, we first present an isothermal solid-phase amplification/detection (ISAD) technique for the detection of single-point mutations that can be performed without labelling in real-time by utilizing both silicon microring-based solid-phase amplification and isothermal recombinase polymerase amplification (RPA). The ISAD technique was performed on a silicon microring device with a plastic chamber containing 10 μL of the reaction mixture, and characterized with an assay for the detection of the HRAS (Harvey RAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 42 publications
2
72
0
Order By: Relevance
“…Prior studies have applied RPA to aptamer ssDNA (single-stranded DNA) (22 ), positive control DNA (23 ), purified DNA (20, 24 -28 ), human genomic DNA (20,26,29 ), double-stranded PCR product (30,31 ), plasmid DNA (27,28 ), cDNA (25,26 ), and spiked plasma (25,32 ), but none have tested RPA with human samples. In contrast, we used actual human samples in our study.…”
Section: © 2014 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Prior studies have applied RPA to aptamer ssDNA (single-stranded DNA) (22 ), positive control DNA (23 ), purified DNA (20, 24 -28 ), human genomic DNA (20,26,29 ), double-stranded PCR product (30,31 ), plasmid DNA (27,28 ), cDNA (25,26 ), and spiked plasma (25,32 ), but none have tested RPA with human samples. In contrast, we used actual human samples in our study.…”
Section: © 2014 American Association For Clinical Chemistrymentioning
confidence: 99%
“…To design MTB-ISAD device, the modified protocol was used for the detailed structure and fabrication of silicon microring resonators (SMR) that have been previously described (Shin et al, 2013a(Shin et al, , 2013b. The device (2.5 cm  0.8 cm) structures such as microring structures, waveguides, and gratings, were patterned on a commercially available 200 mm SOI (Silicon-On-Insulator) wafer with a 220 nm thick top silicon layer and 2 μm thick buried oxide layer by 210 nm deep (ultraviolet) lithography.…”
Section: Mtb-isad Device Fabrication and Operationmentioning
confidence: 99%
“…We also demonstrated the clinical utility of the MTB-ISAD assay by detecting MTB nucleic acid in sputum samples from patients with TB. The technique is based on an isothermal solid-phase amplification/detection (ISAD) assay that combines solid-phase-based isothermal DNA amplification (recombinase polymerase amplification (RPA)) and silicon microring resonator (SMR)-based biophotonic sensors, which do not involve labeling (Shin et al, 2013a). Although the SMRs have been used for direct detection of nucleic acids based on the hybridization mechanism between the capture probe and the target (Bogaerts et al, 2012;Baaske and Vollmer, 2012;Shin et al, 2013bShin et al, , 2013cIqbal et al, 2010), however, the MTB-ISAD technique is based on the amplification and the detection mechanism of nucleic acids that was increased the sensitivity of the nucleic acid detection by the combination.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the enzyme is intended to "substitute" the thermal denaturation step normally performed during PCR amplification. The enzyme along with single stranded binding proteins facilitates the annealing of shift of a silicon micro-ring optical resonator [69]. This allowed the amplification signal to be monitored in realtime providing a lower detection limit of 500 fg×µL -1 .…”
Section: Isothermal Amplification On Microarraysmentioning
confidence: 99%
“…This is due to the fact that the helicase enzyme unwinds ds-DNA thus eliminating the need for thermal denaturation normally employed during PCR thermo-cycling. Shin et al [69] have demonstrated one of the most sophisticated and sensitive approaches for isothermal PCR-like amplification of ds-DNA using a solid-phase immobilized primer. This was carried out using recombinase polymerase amplification (RPA) [70,71] which employs a uvsX recombinase enzyme of specific activity isolated from T4 phage.…”
Section: Isothermal Amplification On Microarraysmentioning
confidence: 99%